Connexin43 gap junctions in normal, regenerating, and cultured mouse bone marrow and in human leukemias: their possible involvement in blood formation - Krenacs, T; Rosendaal, M (The American journal of pathology, 1998)
Communicating channels called gap junctions are thought to play a ubiquitous part in cell growth and development. Based on earlier work, we have recently found functional evidence of their presence in human and mouse bone marrow. In this study we studied the cell-type association of the gap junction channel-forming protein, connexin, in mouse and human bone marrow under different physiological and pathological conditions and tested the pathway of communication in bone marrow cultures. For high-resolution antigen demonstration we took advantage of semi-thin resin sections, antigen retrieval methods, immunofluorescence, and confocal laser scanning microscopy. Connexin43 (Cx43) and its mRNA were consistently expressed in human and rodent marrow. Cx37 was found only in the arteriolar endothelium, but neither Cx32 nor -26 were expressed. In tissue sections, the immunostained junctions appeared as dots, which were digitally measured and counted. Their average size was 0.40 mm in human and 0.49 mm in mice marrow. There were at least twice as many gap junctions in the femoral midshaft of 6-week-old mice (1.75 x 10(5)/mm3) as in those older than 12 weeks (0.89 x 10(5)/mm3). Most Cx43 was associated with collagen III+ endosteal and adventitial stromal cells and with megakaryocytes. Elsewhere, they were few and randomly distributed between all kinds of hematopoietic cells. In the femoral epiphysis of juvenile mice, stromal cell processes full of Cx43 enmeshed three to six layers of hematopoietic cells near the endosteum. The same pattern was seen in the midshaft of regenerating mouse marrow 3 to 5 days after cytotoxic treatment with 5-fluorouracil. Functional tests in cultures showed the transfer of small fluorescent dyes, Lucifer Yellow and 2',7'-bis-(2-carboxyethyl)-5, 6-carboxyfluorescein, between stromal cells and in rare cases between stromal and hematopoietic cells too. The stromal cells were densely packed with Cx43 and we found aggregates of connexon particles in their membrane replicas. In normocellular human bone marrow, gap junctions were as rare as in adult mouse and similarly distributed, except that they were also on adipocytic membranes. In a few leukemic samples, characterized by an increased stromal/hematopoietic cell ratio, there were two- to fourfold more Cx43 (2.8 x 10(5) to 3.9 x 10(5)/mm3) than in the normal (1.0 x 10(5) to 1.2 x 10(5)/mm3). The cases included a hypoplastic acute lymphoblastic leukemia, an acute myeloid leukemia (French-American-British classification M4-5), a case of myelodysplastic syndrome with elevated number of megakaryocytes, and a CD34+ acute hemoblastosis, probably acute myeloid leukemia (French-American-British classification M7). Taken together, our results indicate that direct cell-cell communication may be involved in hematopoiesis, ie, in developmentally active epiphyseal bone marrow and when there is a demand for progenitors in regeneration. However, gap junctions may not play as important a role in resting adult hematopoiesis and in leukemias.